The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.ppat.1004633
|View full text |Cite|
|
Sign up to set email alerts
|

CD8 T Cell Response Maturation Defined by Anentropic Specificity and Repertoire Depth Correlates with SIVΔnef-induced Protection

Abstract: The live attenuated simian immunodeficiency virus (LASIV) vaccine SIVΔnef is one of the most effective vaccines in inducing protection against wild-type lentiviral challenge, yet little is known about the mechanisms underlying its remarkable protective efficacy. Here, we exploit deep sequencing technology and comprehensive CD8 T cell epitope mapping to deconstruct the CD8 T cell response, to identify the regions of immune pressure and viral escape, and to delineate the effect of epitope escape on the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Genome-wide deep sequencing of replicating virus populations was performed as previously described (13). Briefly, viral RNA was isolated from plasma using the MinElute virus spin kit (Qiagen).…”
Section: Animalsmentioning
confidence: 99%
“…Genome-wide deep sequencing of replicating virus populations was performed as previously described (13). Briefly, viral RNA was isolated from plasma using the MinElute virus spin kit (Qiagen).…”
Section: Animalsmentioning
confidence: 99%
“…Recently reported detailed analysis of immune responses and deep sequence characterisation of SIVmac239Δ nef post-vaccination indicated that there is a shift following early, rapid virus escape due to immune pressure to variable regions targeted during the acute phase to a re-focussed immunological response to more conserved epitopes [40]. However, the level of sub-clinical antigenic drive required to deliver such an anentropic state requires clarification, perhaps also in the face of host responses to the vaccine virus, since it was also noted that macaques with undetectable plasma viraemia experienced ongoing sequence evolution of the vaccine virus.…”
Section: Discussionmentioning
confidence: 99%
“…9 Thus, in a recent elegant study authors combined deep sequencing technology and comprehensive CD8 T cell epitope mapping and demonstrated that the initial CD8 T cell response in the acute phase of the live attenuated simian immunodeficiency virus infection (SIVDnef, one of the most effective vaccines in inducing protection against wild-type lentiviral challenge) is mounted predominantly against more variable epitopes, followed by viral escape. 48 Interestingly, epitope escape expands the CD8 T cell repertoire that targets highly conserved epitopes (defined as anentropic specificity) generating de novo responses to the escaped epitope variants during the vaccination period. 48 The first and the second waves of HIV vaccine development, aimed to induce nAbs and CTL response, respectively, did not address the issue of antigenic variability, and candidate vaccines' capacity to induce immune responses able to recognize variant (mutated) epitopes has not been tested.…”
Section: Hivmentioning
confidence: 99%
“…48 Interestingly, epitope escape expands the CD8 T cell repertoire that targets highly conserved epitopes (defined as anentropic specificity) generating de novo responses to the escaped epitope variants during the vaccination period. 48 The first and the second waves of HIV vaccine development, aimed to induce nAbs and CTL response, respectively, did not address the issue of antigenic variability, and candidate vaccines' capacity to induce immune responses able to recognize variant (mutated) epitopes has not been tested. 42,[49][50][51] Clinical trials were halted because of lack of efficacy, and subsequent careful statistical analysis demonstrated that in some cases vaccination in fact enhanced HIV acquisition.…”
Section: Hivmentioning
confidence: 99%